Eksistensi Muslimah Sebagai Pillars of Positive-Digital Change melalui Ibrah Sayyidah Fatimah Azzahra - Endiana, Yeni; Ningsih, Yuni Setya; Fauziyah, Ni'matul; Nuruzzaman, Muhammad Adib (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
If a woman is virtuous, then the state is virtuous, and if a woman is not virtuous, then the state is broken. Women serve as the pillars of civilization, consistently contributing to the construction of societal order throughout history, including in the digital era. This research aims to explore the role of Muslim women as pillars of positive digital change and their connection with the lessons from Sayyidah Fatimah Azzahra. Using a descriptive quantitative approach, data for this study was collected through a questionnaire distributed to 64 respondents via Google Forms, along with a brief survey distributed through the Not Gonna Lie (NGL) application. Then the data is analyzed using cluster analysis techniques to group respondents or information into groups that have similarities in attitudes, behaviors, or views related to the existence of Muslim women and ibrah Sayyidah Fatimah Azzahra. The findings reveal that the existence of Muslim women as pillars of positive digital change encompasses: 1) Their presence in propagating Islamic teachings on social media, 2) Their role in maintaining modesty in online interactions, and 3) Their commitment to observing modesty in attire. The correlation with the lessons from Sayyidah Fatimah Azzahra includes: 1) Exemplary worship practices, 2) Self-exemplification, and 3) Exemplification in interactions with others. It is anticipated that this research will inspire and motivate Muslim women to actively contribute as pillars of positive change in the digital sphere in the future.